Feasibility study of prospective gated tomosynthesis using a wide-angle carbon nanotube enabled, stationary digital chest tomosynthesis scanner: In-vivo evaluation in a porcine subject - Alex Billingsley; Christina Inscoe; Jianping Lu; Otto Zhou; Yueh Z. Lee (PLoS ONE, 2026)
Background Tomosynthesis offers a valuable alternative to computed tomography (CT) in longitudinal studies for dose reduction and applications where CT is not an option. This study aimed to demonstrate the performance of physiological gated tomosynthesis on the wide-angle-, carbon nanotube (CNT) x-ray based, stationary digital chest tomosynthesis system (s-DCT). Physiologic gating allows for image quality improvements by reducing motion blur and expands the potential applications. Methods Prospective physiological gating was implemented on the system and a porcine subject was imaged under various gating strategies. Respiratory-only, cardiac-only (breath-hold), and dual gated scans were acquired along with breath-hold-only and free-breathing scans to study independent and joint gating performance. Quantitative analysis was performed by measuring full-width-at-half-maximum (FWHM) from the derivative of line profiles across the edge of the heart wall and diaphragm. Results Dual gating had the highest image quality performance both qualitatively and quantitatively. No significant difference was observed between expiratory phase respiratory gating and breath hold, and during breath hold, cardiac gating significantly improved heart wall FWHM. All gated acquisitions performed better overall than free breathing. Conclusions This study successfully demonstrated physiologic gating on the second-generation s-DCT system with high-quality images and imaging times similar to predicted.